Mutagenic Effectiveness and Efficiency of Gamma ( ) Rays and Ethyl Methane Sulphonate on Bougainvillea spectabilis Willd. (cv. Lalbagh) - Anitha, K.; Surendranath, R.; Jawaharlal, M.; Ganga, M. (International Journal of Bio-resource and Stress Management, 2017)
Mutation breeding is an established method used for crop improvement and has played a major role in the development of many new flower colour shape mutant cultivars in ornamentals. The present study was undertaken to induce mutations in Bougainvillea spectabilis Willd. cv. Lalbaghusing a physical mutagen ( rays) and a chemical mutagen (Ethyl Methane Sulphonate) for creating novelty during 2014–15 at TNAU, Coimbatore, Tamilnadu, India. Hardwood cuttings were treated with three doses of -rays (5.0, 7.5, 10.0 Gy) and three concentrations of Ethyl Methane Sulphonate (0.8, 0.9 and 1.0%). The first mutant-vegetative (M1V1) generation was evaluated for various morphological traits. Sprouting percentage and survival rate of seedlings gradually reduced with proportional increase in dose concentration of mutagens. All the morphological traits recorded a declining trend with increasing mutagenic treatments. Some of the morphological mutants’ viz., dwarfness, early flowering and thornless stem were noticed within the mutagen treated plant population. Nine different types of chlorophyll mutants were observed namely albina, albina green, xantha, chlorina, viridis, yellow viridis, striata, maculata andvariegated type. Among the chlorophyll mutants recorded, chlorina was more predominant followed by maculata and viridis. With regard to mutagenic treatments, EMS 1.0% recorded more number of morphological mutants (12 Nos.) and chlorophyll mutants (20 Nos.). The 5.0 Gy dosage of -radiation recorded the highest mutagenic effectiveness (215.20) and efficiency (122.69) than other treatments. The highest mutation rates in terms of effectiveness (161.81) and efficiency (75.62) were recorded in EMS than -radiation in Bougainvillea cv. Lalbagh.